Evidence for Resilient Agriculture informs over USD 1 billion in investment plans and 3 subnational adaptation plans - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
The Evidence for Resilient Agriculture (ERA), created by ICRAF together with partners, is a meta-data set and analytical engine that uses the last 40 years of agricultural research in Africa to predict productivity, resilience and greenhouse gas emission impacts when switching from one farming technology to another.